A CEO's future temporal depth and organizational resilience - Maximilian Weis; Patricia Klarner (Schmalenbach Journal of Business Research (SBUR), 2022)
Scholars have long investigated the organizational antecedents of resilience, but less is known about CEO-level antecedents. This is surprising, since upper echelons research suggests that a CEO influences major firm decisions. Addressing this gap in our knowledge, we suggest that a CEO prepares for and adjusts to unexpected events in the environment on the basis of the individual future temporal depth (FTD). It reflects the temporal distance into the future that a CEO usually takes into consideration when contemplating future events. Our study of CEOs of 462 S&P500 firms during the Global Financial Crisis and the COVID-19 pandemic shows that a CEO's longer FTD is associated with less severe economic losses but with a longer recovery time from adversity. If such a CEO can draw on a functionally diverse TMT, the losses are less severe, while prior organizational crisis experience reduces the recovery time. Our paper contributes to organizational resilience research by uncovering its cognitive underpinnings and offering a contextual learning perspective on organizational resilience. We also contribute to upper echelons research by unveiling a CEO's role in preparing for and adjusting to adversity.
Keywords: 650; CEO temporal cognition; Upper Echelons; Organizational crisis; Organizational resilience